Silicon oxide-supported single-atom copper material, preparation method thereof, and application in electrochemical reduction treatment of chloramphenicol

By using silicon oxide-supported single-atom copper material as a catalyst in electrochemical reduction reaction, the high cost, complex processes and by-product toxicity of removing chloramphenicol in the prior art is solved, and efficient and economical chloramphenicol is achieved. The effect of removing the carbon dioxide and conforms to the concept of green economy.

CN115814795BActive Publication Date: 2025-02-14UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211636628.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-02-14
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, complex processes, high pH dependence and high toxicity of by-products when removing chloramphenicol, making it difficult to achieve an efficient and economical removal method.

Method used

Silicon oxide-supported single-atom copper material is used as the electrode catalyst to efficiently remove chloramphenicol through electrochemical reduction and dechlorination reaction, inhibit the aggregation of metal atoms using interface restriction strategies, design active sites to anchor single-atom copper, and use silicon dioxide The gap and coordination bonds enhance the stability and active surface area of ​​the catalyst.

Benefits of technology

It has achieved rapid and efficient removal of chloramphenicol under electrochemical reduction conditions, with a wide pH range and low cost, which is in line with the concept of green economy and sustainable development, and the chemical and electrochemical stability of the catalyst is improved and the active surface area is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003994086830000011
    Figure HDA0003994086830000011
  • Figure HDA0003994086830000012
    Figure HDA0003994086830000012
  • Figure HDA0003994086830000021
    Figure HDA0003994086830000021
Patent Text Reader

Abstract

The present invention provides a method for preparing a silicon oxide-supported single-atom copper material. Compared with the prior art, the present invention suppresses the aggregation of metal atoms through an interface restriction strategy to obtain a silicon oxide-supported single-atom copper material. The material is amorphous silicon oxide-supported single-atom copper. The copper element has excellent electro-reduction dechlorination activity, and the active sites are designed in a targeted manner. The silicon dioxide gaps and rich coordination bonds generated in situ are cleverly used to anchor the single-atom copper. At the same time, two-dimensional porous silicon dioxide is used as a carrier, which not only improves the chemical and electrochemical stability of the catalyst, but also increases the active surface area of ​​the catalyst, thereby comprehensively improving the electrochemical performance of the catalyst, achieving the effect of dechlorination and detoxification in a short time, and its applicable pH range is wide, and the electrode material used in the present invention is a non-precious metal with a wide source, low cost, and in line with the concept of green economy and sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry and functional materials, and in particular relates to a silicon oxide-loaded single-atom copper material, a preparation method thereof, and an application thereof in electrochemical reduction treatment of chloramphenicol. Background Art

[0002] In the past few decades, antibiotics have played an irreplaceable role in the treatment of diseases and are widely used in human medicine, veterinary medicine and animal husbandry. However, the abuse of antibiotics and inappropriate treatments lead to the accumulation of antibiotics and the proliferation of antibiotic resistance genes, posing a threat to human health and the ecosystem. Among them, chloramphenicol is one of the most common drugs. As a broad-spectrum antibiotic, it has been widely used. Studies have shown that chloramphenicol ingested into the human body through food chain enrichment may cause anemia, neuromuscular disorders and other diseases. Therefore, the development of an efficient removal method for chloramphenicol is extremely important for both human health and the ecological environment.

[0003] At present, the common chloramphenicol degradation methods all have some defects to a greater or lesser extent. The traditional adsorption method is a typical physical technology, but it cannot achieve the purpose of removing antibiotics and it is difficult to achieve efficient detoxification of chloramphenicol. Advanced oxidation methods, photocatalysis and other technologies require special reaction devices, are highly dependent on pH, generate sludge, and may produce more toxic by-products. In contrast, the electrocatalytic reduction dechlorination method has broad prospects, and it has the advantages of mild reaction conditions, fast reaction speed, and no secondary pollution.

[0004] Electrode materials are an important factor affecting the efficiency of electrocatalytic reduction dechlorination. Precious metal palladium-based composite materials are often used as catalysts in electrocatalytic dechlorination reactions, but the cost of precious metal catalysts is high and cannot be used in large-scale production. Therefore, it is very important to develop low-cost and simple preparation process electrode materials for efficient reduction and removal of chloramphenicol. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a silicon oxide-loaded single-atom copper material, a preparation method thereof and an application in the electrochemical reduction treatment of chloramphenicol. The silicon oxide-loaded single-atom copper material can efficiently and quickly degrade chloramphenicol by dechlorination under electrochemical reduction conditions.

[0006] The present invention provides a method for preparing a silicon oxide-supported single-atom copper material, comprising the following steps:

[0007] S1) mixing the copper multi-component complex and the carbon nanomaterial in a solvent to obtain a suspension;

[0008] S2) mixing the suspension with a silicon source to obtain an intermediate;

[0009] S3) thermally decomposing the intermediate in a protective atmosphere to remove the ligand and thermally decomposing the intermediate in an oxidizing atmosphere to remove the carbon nitride, thereby obtaining a silicon oxide-supported single-atom copper material.

[0010] Preferably, the copper multi-component complex is prepared according to the following method:

[0011] The multidentate ligand and the copper salt are mixed and stirred in an organic solvent to obtain a multi-component copper complex;

[0012] The multidentate ligand is selected from one or more of terpyridine, phthalocyanine and porphyrin; the copper salt is selected from one or more of copper sulfate, copper nitrate and copper acetate; the molar ratio of the multi-ligand to the copper ion in the copper salt is (1-3):1.

[0013] Preferably, the carbon nanomaterial is selected from carbon nitride nanomaterials and / or carbon nanotubes;

[0014] The carbon nitride nanomaterial is prepared according to the following method:

[0015] Calcining urea in air to obtain carbon nitride;

[0016] The heating rate of the calcination is 3-7°C / min; the calcination temperature is 500°C-650°C; and the calcination time is 1-3h.

[0017] Preferably, the mass ratio of the copper multi-component complex to the carbon nitride nanomaterial is 1:(20-40);

[0018] The silicon source is tetraethyl orthosilicate;

[0019] The mass ratio of the silicon source to the copper multi-component complex is (700-2000):1.

[0020] Preferably, the mixing time in step S1) is 18 to 30 hours; and the mixing time in step S2) is 8 to 15 hours.

[0021] Preferably, in the step S3), the temperature of pyrolysis in a protective atmosphere is 200°C to 350°C; the time of pyrolysis in a protective atmosphere is 0.5 to 2 hours; the temperature of pyrolysis in an oxidizing atmosphere is 500°C to 700°C; the time of pyrolysis in an oxidizing atmosphere is 1 to 3 hours; and the oxidizing atmosphere is air.

[0022] The present invention also provides a silicon oxide-supported single-atom copper material prepared by the above preparation method, wherein the silicon oxide-supported single-atom copper material has a lamellar structure.

[0023] The present invention also provides an application of the silicon oxide-supported single-atom copper material prepared by the above preparation method in the electrochemical reduction treatment of chloramphenicol.

[0024] The present invention also provides a method for electrochemical reduction treatment of chloramphenicol, comprising the following steps:

[0025] The silicon oxide-supported single-atom copper material prepared by the above preparation method is supported on a conductive substrate to obtain a silicon oxide-supported single-atom copper material electrode;

[0026] Using a silicon oxide-supported single-atom copper material electrode as the cathode, an electrochemical dechlorination reaction is carried out in an electrolyte containing chloramphenicol.

[0027] Preferably, the loading amount of the silicon oxide-supported single-atom copper material in the silicon oxide-supported single-atom copper material electrode is 0.1 to 1 mg / cm 2 ;

[0028] The chloramphenicol-containing electrolyte is a chloramphenicol-containing potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution.

[0029] The invention provides a preparation method of a silicon oxide supported single-atom copper material, comprising the following steps: S1) mixing a multi-component complex of copper and a carbon nanomaterial in a solvent to obtain a suspension; S2) mixing the suspension with a silicon source to obtain an intermediate; S3) pyrolyzing the intermediate in a protective atmosphere to remove a ligand and pyrolyzing the intermediate in an oxidizing atmosphere to remove carbon nitride to obtain the silicon oxide supported single-atom copper material. Compared with the prior art, the present invention suppresses the aggregation of metal atoms through an interface restriction strategy to obtain a silicon oxide-supported single-atom copper material. The material is amorphous silicon oxide-supported single-atom copper. The material utilizes the excellent electro-reduction dechlorination activity of the copper element to design active sites in a targeted manner, cleverly utilizes the in-situ generated silicon dioxide gaps and abundant coordination bonds to anchor the single-atom copper, and uses two-dimensional porous silicon dioxide as a carrier, which not only improves the chemical and electrochemical stability of the catalyst, but also increases the active surface area of ​​the catalyst, thereby comprehensively improving the electrochemical performance of the catalyst, achieving the effect of dechlorination and detoxification in a short time, and having a wide applicable pH range. In addition, the electrode material used in the present invention is a non-precious metal with a wide source, low cost, and in line with the concept of green economy and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the silicon oxide-supported single-atom copper material Cu-SiO2 obtained in Example 1 of the present invention;

[0031] Figure 2 This is a transmission electron microscope image of the silicon oxide-supported single-atom copper material Cu-SiO2 obtained in Example 1 of the present invention;

[0032] Figure 3 is the X-ray diffraction pattern of the silicon oxide-supported single-atom copper material Cu-SiO2 obtained in Inventive Example 1;

[0033] Figure 4 This is a diagram showing the conversion and dechlorination effect of chloramphenicol by electrochemical reduction dechlorination of the silicon oxide-supported single-atom copper material obtained in Example 1 of the present invention;

[0034] Figure 5 The chloramphenicol conversion and dechlorination effect diagram of Examples 1 to 3 of the present invention;

[0035] Figure 6 The chloramphenicol conversion and dechlorination effect diagram of Example 4 of the present invention;

[0036] Figure 7 This is a diagram showing the conversion and dechlorination of chloramphenicol in Example 5 of the present invention;

[0037] Figure 8 This is a diagram showing the conversion and dechlorination of chloramphenicol in Example 6 of the present invention;

[0038] Fig. 9 This is a diagram showing the conversion and dechlorination of chloramphenicol in Example 7 of the present invention;

[0039] Fig.10 This is a diagram showing the conversion and dechlorination effects of chloramphenicol in Example 8 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] The invention provides a preparation method of a silicon oxide supported single-atom copper material, comprising the following steps: S1) mixing a multi-component complex of copper and a carbon nanomaterial in a solvent to obtain a suspension; S2) mixing the suspension with a silicon source to obtain an intermediate; S3) pyrolyzing the intermediate in a protective atmosphere to remove a ligand and pyrolyzing the intermediate in an oxidizing atmosphere to remove carbon nitride to obtain the silicon oxide supported single-atom copper material.

[0042] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0043] In the present invention, the ligand in the multi-component complex of copper can be a multi-dentate ligand well known to those skilled in the art, without any special restrictions, and preferably one or more of terpyridine, phthalocyanine and porphyrin in the present invention; the multi-component complex of copper can be prepared according to a method well known to those skilled in the art, without any special restrictions, and preferably prepared according to the following method: the multi-component ligand and a copper salt are mixed and stirred in an organic solvent to obtain a multi-component complex of copper; the copper salt is preferably one or more of copper sulfate, copper nitrate and copper acetate; the molar ratio of the multi-component ligand to the copper ion in the copper salt is preferably (1-3):1, more preferably (1-2):1, and more preferably 1:1; the organic solvent can be an organic solvent well known to those skilled in the art, without any special restrictions, and preferably tetrahydrofuran in the present invention; the mixing and stirring is preferably carried out at room temperature; the mixing and stirring time is preferably 18-30h, more preferably 20-26h, and more preferably 24-26h; after mixing and stirring, the copper multi-component complex is preferably obtained by centrifugation, washing and drying; the washing is preferably carried out using pentane.

[0044] The carbon nanomaterial can be any carbon nanomaterial well known to those skilled in the art without any special restrictions. In the present invention, it is preferably a carbon nitride nanomaterial and / or a carbon nanotube; the carbon nitride nanomaterial is prepared according to the following method: calcining urea in air to obtain carbon nitride; the heating rate of the calcination is preferably 3-7°C / min, more preferably 4-6°C / min, and more preferably 5°C / min; the calcination temperature is preferably 500°C-650°C, more preferably 550°C-600°C; the calcination time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h. In the present invention, unless otherwise specified, the calcination time refers to the holding time. After calcination, it is preferably ground to obtain carbon nitride.

[0045] A copper multi-complex and a carbon nitride nanomaterial are mixed in a solvent to obtain a suspension; the mass ratio of the copper multi-complex to the carbon nitride nanomaterial is preferably 1:(20-40), more preferably 1:(25-35), and more preferably 1:30; the solvent is any solvent well known to those skilled in the art and is not particularly limited. In the present invention, an alcohol solvent is preferably used, and ethanol is more preferably used; the mixing time is preferably 18-30 hours, more preferably 20-26 hours, and more preferably 24-26 hours; the copper multi-complex is impregnated into the carbon nitride nanomaterial by mixing.

[0046] The suspension is mixed with a silicon source to obtain an intermediate; the silicon source is preferably a silicate, more preferably tetraethyl orthosilicate; the mass ratio of the silicon source to the copper multi-component complex is preferably (700-2000):1, more preferably (700-1800):1, more preferably (790-1600):1, and most preferably (790-1585):1; the mixing time is preferably 8-15h, more preferably 10-14h, and more preferably 12h; after mixing, filtering and drying to obtain an intermediate.

[0047] The intermediate is sequentially pyrolyzed in a protective atmosphere to remove the ligand, and pyrolyzed in an oxidizing atmosphere to remove the carbon nitride, to obtain a silicon oxide-supported single-atom copper material; the protective atmosphere can be any protective atmosphere well known to those skilled in the art, and is not particularly limited, and is preferably nitrogen in the present invention; the temperature of the pyrolysis in the protective atmosphere is preferably 200°C to 350°C, more preferably 230°C to 330°C, more preferably 240°C to 300°C, and most preferably 250°C; the time of the pyrolysis in the protective atmosphere is preferably 0.5 to 2h, more preferably 0.8 to 1.5h, and more preferably 1 to 1.2 h; the volume content of oxygen in the oxidizing atmosphere is preferably 15% to 30%, more preferably 15% to 25%, and more preferably 20% to 21%; in the present invention, the oxidizing atmosphere is preferably air; the temperature of pyrolysis in the oxidizing atmosphere is preferably 500°C to 700°C, more preferably 500°C to 650°C, more preferably 500°C to 600°C, more preferably 530°C to 600°C, and most preferably 550°C to 600°C; the time of pyrolysis in the oxidizing atmosphere is preferably 1 to 3 h, more preferably 1 to 2.5 h, and more preferably 1 to 2 h.

[0048] The present invention suppresses the aggregation of metal atoms through an interface restriction strategy to obtain a silicon oxide-supported single-atom copper material. The material is amorphous silicon oxide-supported single-atom copper. The material utilizes the excellent electro-reduction dechlorination activity of the copper element to design active sites in a targeted manner, cleverly utilizes the in-situ generated silicon dioxide gaps and abundant coordination bonds to anchor the single-atom copper, and simultaneously uses two-dimensional porous silicon dioxide as a carrier, which not only improves the chemical and electrochemical stability of the catalyst, but also increases the active surface area of ​​the catalyst, thereby comprehensively improving the electrochemical performance of the catalyst, achieving the effect of dechlorination and detoxification in a short time, and having a wide applicable pH range. In addition, the electrode material used in the present invention is a non-precious metal with a wide source, low cost, and in line with the concepts of green economy and sustainable development.

[0049] The present invention also provides a silicon oxide-supported single-atom copper material prepared by the above method, wherein the silicon oxide-supported single-atom copper material has a lamellar structure.

[0050] Specifically, the silicon nitride-supported single-atom copper material uses silicon dioxide with a two-dimensional porous morphology as a carrier; single-atom copper is anchored in the gaps of the silicon dioxide.

[0051] The present invention also provides an application of the silicon oxide-supported single-atom copper material prepared by the above method in the electrochemical reduction treatment of chloramphenicol.

[0052] The present invention also provides a method for electrochemical reduction treatment of chloramphenicol, comprising the following steps: loading the silicon oxide loaded single-atom copper material prepared by the above-mentioned preparation method on a conductive substrate to obtain a silicon oxide loaded single-atom copper material electrode; using the silicon oxide loaded single-atom copper material electrode as a cathode, and performing an electrochemical dechlorination reaction in an electrolyte containing chloramphenicol.

[0053] The silicon oxide-supported single-atom copper material prepared by the above preparation method is supported on a conductive substrate to obtain a silicon oxide-supported single-atom copper material electrode; the conductive substrate can be any conductive substrate well known to those skilled in the art without any special restrictions, and is preferably carbon paper in the present invention; the loading method can be any method well known to those skilled in the art without any special restrictions, and is preferably loaded according to the following method in the present invention: the silicon oxide-supported single-atom copper material is dispersed with a dispersion liquid, and then uniformly coated or dripped onto the surface of the conductive substrate, and dried to obtain a silicon oxide-supported single-atom copper material electrode; the dispersion liquid is preferably an alcohol-water mixture, and more preferably a mixed solution of ethanol and water; the volume ratio of the alcohol solvent to water in the alcohol-water mixture is preferably (1-2):1, and more preferably 1.5:1; the loading amount of the silicon oxide-supported single-atom copper material in the silicon oxide-supported single-atom copper material electrode is preferably 0.1-1 mg / cm 2 , more preferably 0.2 to 0.8 mg / cm 2 , and more preferably 0.3 to 0.6 mg / cm 2 , and most preferably 0.4 to 0.5 mg / cm 2 .

[0054] An electrochemical dechlorination reaction is carried out in a chloramphenicol-containing electrolyte with a silicon oxide-loaded single-atom copper material electrode as a cathode; the chloramphenicol-containing electrolyte is preferably a potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution containing chloramphenicol; the concentration of the potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution is preferably 0.05-0.08 mol / L, more preferably 0.06-0.07 mol / L, and even more preferably 0.067 mol / L; the pH value of the potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution is preferably 5-8, more preferably 6-8; the concentration of chloramphenicol in the chloramphenicol-containing electrolyte is preferably less than or equal to 80 mg / L; in the embodiment provided by the present invention, the concentration of chloramphenicol in the chloramphenicol-containing electrolyte is specifically described as 50 mg / L; in the present invention, the electrochemical dechlorination reaction is preferably carried out with metal platinum as the voltage of the electrochemical dechlorination reaction is preferably -1.0-1.0 V; the time of the electrochemical dechlorination reaction is preferably 2-3 h.

[0055] To further illustrate the present invention, a silicon oxide-supported single-atom copper material, a preparation method thereof, and an application thereof in the electrochemical reduction treatment of chloramphenicol provided by the present invention are described in detail below in conjunction with embodiments.

[0056] The reagents used in the following examples are all commercially available.

[0057] Example 1

[0058] 1.1 Preparation of Cu-SiO2 material: 20g of urea was placed in a muffle furnace and heated to 550℃ at a heating rate of 5℃ / min. The temperature was kept constant for 2h to obtain blocky C3N4, which was ground into powder with a mortar. 0.125mM terpyridine and 0.125mM Cu(OAc)2·H2O were added to 20mL tetrahydrofuran and stirred at room temperature for 24h. The resulting green precipitate was centrifuged, then washed twice with pentane and dried in an oven to obtain the copper complex Cu(Tpy)2. 400mg C3N4 and 13mg Cu(Tpy)2 were weighed and dispersed in 200mL anhydrous ethanol. After stirring for 24h, 22mL ethyl silicate was added and continued to stir for 12h, then filtered and dried to obtain a light yellow solid powder Cu(Tpy)2 / C3N4@SiO2. The light yellow solid powder Cu(Tpy)2 / C3N4@SiO2 was first pyrolyzed in a N2 atmosphere at 250°C for 1 h to remove the ligand, and then pyrolyzed in an air atmosphere at 550°C for 2 h to remove the C3N4 substrate to obtain the silicon oxide-supported single-atom copper material Cu-SiO2.

[0059] Preparation of silicon oxide supported single atom copper catalyst electrode (Cu-SiO2 / CP): Weigh 2 mg of Cu-SiO2 material and disperse it in a mixed solution of ethanol and water with a volume ratio of 3:2 to obtain a dispersion, evenly drop it on the washed and dried carbon paper (CP), and use it as a cathode material after drying.

[0060] Electrochemical reduction dechlorination: Weigh 5 mg of chloramphenicol and dissolve it in 100 mL of 0.067 M potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution with a pH of 6.0. Use a platinum wire as the anode and silver / silver chloride as the reference electrode. Apply a voltage of -1.0 V to carry out the electrochemical reaction for 3 hours.

[0061] The silicon oxide supported single atom copper material Cu-SiO2 obtained in Example 1 was analyzed by scanning electron microscopy, and its scanning electron microscopy image was obtained as follows: Figure 1 shown.

[0062] The silicon oxide supported single atom copper material Cu-SiO2 obtained in Example 1 was analyzed using a transmission electron microscope, and its transmission electron microscope image was obtained as follows: Figure 2 shown.

[0063] The silicon oxide supported single atom copper material Cu-SiO2 obtained in Example 1 was analyzed by X-ray diffraction, and its X-ray diffraction pattern was obtained as follows: Figure 3 shown.

[0064] Chloramphenicol and chloride ion concentration detection: Sampling was performed at fixed time intervals, and chloramphenicol and chloride ion were detected using Agilent-1290 ultra high performance liquid chromatograph and Dion ion chromatograph ICS-1000, respectively, to obtain the chloramphenicol conversion and dechlorination effect diagram of the electrochemical reduction dechlorination of the silicon oxide-supported single-atom copper material obtained in Example 1.

[0065] Example 2

[0066] The pH value of the electrolyte was adjusted to 7.0, and other implementation conditions were the same as in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were as follows: Figure 5 .

[0067] Example 3

[0068] The pH value of the electrolyte was adjusted to 8.0, and other implementation conditions were the same as in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were as follows: Figure 5 .

[0069] Example 4

[0070] The same carbon paper was used to test the cycle stability of the catalyst electrode. Other implementation conditions were the same as in Example 1. The removal effect and dechlorination effect of chloramphenicol in five cycles were shown in FIG. Figure 6 .

[0071] Depend on Figure 1 ,2It can be seen that Cu-SiO2 material has a lamellar structure and has a higher catalytic active specific surface area. Figure 4It can be seen that Cu-SiO2 has excellent catalytic activity in reducing chloramphenicol, and can reduce 100% of chloramphenicol within three hours, and its dechlorination rate reaches 100%. Figure 5 It can be seen that the Cu-SiO2 electrocatalytic system has a wide pH application range. Compared with neutral and alkaline conditions, the reduction effect of chloramphenicol is best under acidic conditions. 100% of chloramphenicol can be reduced within two hours, and the dechlorination effect is further improved, and the dechlorination rate can reach 100% within three hours.

[0072] Example 5

[0073] 0.125mM terpyridine and 0.125mM Cu(OAc)2·H2O were added to 20mL tetrahydrofuran and stirred at room temperature for 24h. The resulting green precipitate was centrifuged, then washed twice with pentane and dried in an oven to obtain the copper complex Cu(Tpy)2. 400mg of commercial carbon nanotubes CNTs and 13mg of Cu(Tpy)2 were weighed and dispersed in 200mL of anhydrous ethanol. After stirring for 24h, 22mL of ethyl silicate was added and continued to stir for 12h, then filtered and dried to obtain a black solid powder Cu(Tpy)2 / CNTs@SiO2. The black solid powder Cu(Tpy)2 / CNTs@SiO2 was first pyrolyzed at 250℃ in N2 atmosphere for 1h to remove the ligand, and then pyrolyzed at 600℃ in air atmosphere for 1h to remove the CNTs substrate to obtain a silicon oxide-supported single-atom copper material. The electrode preparation and electrochemical dechlorination conditions were the same as those in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were as follows: Figure 7 .

[0074] Example 6

[0075] Place 20g of urea in a muffle furnace and heat to 550℃ at a heating rate of 5℃ / min. Keep the temperature constant for 2h to obtain blocky C3N4, which is ground into powder in a mortar. Add 0.125mM terpyridine and 0.125mM CuSO4·5H2O to 20mL tetrahydrofuran and stir at room temperature for 24h. Centrifuge the resulting green precipitate, then wash twice with pentane and dry in an oven to obtain the copper complex Cu(Tpy)2. Weigh 400mg C3N4 and 13mg Cu(Tpy)2 and disperse them in 200mL anhydrous ethanol. After stirring for 24h, add 22mL ethyl silicate and continue stirring for 12h, then filter and dry to obtain a light yellow solid powder Cu(Tpy)2 / C3N4@SiO2. The light yellow solid powder Cu(Tpy)2 / C3N4@SiO2 was first pyrolyzed in N2 atmosphere at 250℃ for 1h to remove the ligand, and then pyrolyzed in air atmosphere at 550℃ for 2h to remove the C3N4 substrate to obtain silicon oxide supported single atom copper material. The electrode preparation and electrochemical dechlorination conditions were the same as those in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were observed. Figure 8.

[0076] Example 7

[0077] Preparation of Cu-SiO2 material: 20g of urea was placed in a muffle furnace, heated to 550℃ at a heating rate of 5℃ / min, and kept at this temperature for 2h to obtain blocky C3N4, which was ground into powder with a mortar. 0.125mM terpyridine and 0.125mM Cu(OAc)2·H2O were added to 20mL tetrahydrofuran and stirred at room temperature for 24h. The resulting green precipitate was centrifuged, then washed twice with pentane and dried in an oven to obtain the copper complex Cu(Tpy)2. 400mg C3N4 and 13mg Cu(Tpy)2 were weighed and dispersed in 200mL anhydrous ethanol. After stirring for 24h, 22mL ethyl silicate was added and continued to stir for 12h, then filtered and dried to obtain a light yellow solid powder Cu(Tpy)2 / C3N4@SiO2. The light yellow solid powder Cu(Tpy)2 / C3N4@SiO2 was first pyrolyzed in N2 atmosphere at 250℃ for 1h to remove the ligand, and then pyrolyzed in air atmosphere at 550℃ for 1.5h to remove the C3N4 substrate to obtain a silicon oxide-supported single-atom copper material. The electrode preparation and electrochemical dechlorination conditions were the same as those in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were observed. Fig. 9 .

[0078] Example 8

[0079] Preparation of Cu-SiO2 material: 20g of urea was placed in a muffle furnace, heated to 550℃ at a heating rate of 5℃ / min, and kept at this temperature for 2h to obtain blocky C3N4, which was ground into powder with a mortar. 0.125mM terpyridine and 0.125mM Cu(OAc)2·H2O were added to 20mL tetrahydrofuran and stirred at room temperature for 24h. The resulting green precipitate was centrifuged, then washed twice with pentane and dried in an oven to obtain the copper complex Cu(Tpy)2. 400mg C3N4 and 13mg Cu(Tpy)2 were weighed and dispersed in 200mL anhydrous ethanol. After stirring for 24h, 11mL ethyl silicate was added and continued to stir for 12h, then filtered and dried to obtain a light yellow solid powder Cu(Tpy)2 / C3N4@SiO2. The light yellow solid powder Cu(Tpy)2 / C3N4@SiO2 was first pyrolyzed in N2 atmosphere at 250℃ for 1h to remove the ligand, and then pyrolyzed in air atmosphere at 550℃ for 2h to remove the C3N4 substrate to obtain silicon oxide supported single atom copper material. The electrode preparation and electrochemical dechlorination conditions were the same as those in Example 1. The removal effect and dechlorination effect of chloramphenicol within three hours were observed. Fig.10 .

Claims

1. A method for preparing a silicon oxide-supported single-atom copper material, characterized in that: The following steps are involved: S1) mixing the copper multi-component complex and the carbon nanomaterial in a solvent to obtain a suspension; S2) mixing the suspension with a silicon source to obtain an intermediate; S3) pyrolyzing the intermediate in a protective atmosphere to remove the multi-component complex and pyrolyzing it in an oxidizing atmosphere in sequence to obtain a silicon oxide-supported single-atom copper material; The carbon nanomaterial is selected from carbon nitride nanomaterials and / or carbon nanotubes.

2. The preparation method according to claim 1, characterized in that: The multi-component complex of copper is prepared according to the following method: The multidentate ligand and the copper salt are mixed and stirred in an organic solvent to obtain a multi-component copper complex; The multidentate ligand is selected from one or more of terpyridine, phthalocyanine and porphyrin; the copper salt is selected from one or more of copper sulfate, copper nitrate and copper acetate; the molar ratio of the multidentate ligand to the copper ion in the copper salt is (1-3):

1.

3. The preparation method according to claim 1, characterized in that: The carbon nitride nanomaterial is prepared according to the following method: Calcining urea in air to obtain carbon nitride; The heating rate of the calcination is 3-7°C / min; the calcination temperature is 500°C-650°C; and the calcination time is 1-3h.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the copper multi-component complex to the carbon nitride nanomaterial is 1:(20-40); The silicon source is tetraethyl orthosilicate; The mass ratio of the silicon source to the copper multi-component complex is (700-2000):

1.

5. The preparation method according to claim 1, characterized in that: The mixing time in step S1) is 18 to 30 hours; the mixing time in step S2) is 8 to 15 hours.

6. The preparation method according to claim 1, characterized in that: In the step S3), the temperature of pyrolysis in a protective atmosphere is 200°C to 350°C; the time of pyrolysis in a protective atmosphere is 0.5 to 2 hours; the temperature of pyrolysis in an oxidizing atmosphere is 500°C to 700°C; the time of pyrolysis in an oxidizing atmosphere is 1 to 3 hours; the oxidizing atmosphere is air.

7. A silicon oxide-supported single-atom copper material prepared by the preparation method according to any one of claims 1 to 6, wherein the silicon oxide-supported single-atom copper material has a lamellar structure.

8. Use of the silicon oxide-supported single-atom copper material prepared by the preparation method according to any one of claims 1 to 6 in the electrochemical reduction treatment of chloramphenicol.

9. A method for electrochemical reduction treatment of chloramphenicol, characterized in that: The following steps are involved: The silicon oxide-supported single-atom copper material prepared by any one of the preparation methods of claims 1 to 6 is supported on a conductive substrate to obtain a silicon oxide-supported single-atom copper material electrode; Using a silicon oxide-supported single-atom copper material electrode as the cathode, an electrochemical dechlorination reaction is carried out in an electrolyte containing chloramphenicol.

10. The method according to claim 9, characterized in that The loading amount of the silicon oxide-supported single-atom copper material in the silicon oxide-supported single-atom copper material electrode is 0.1 to 1 mg / cm 2 ; The chloramphenicol-containing electrolyte is a chloramphenicol-containing potassium dihydrogen phosphate-disodium hydrogen phosphate buffer solution.

Citation Information

Patent Citations

  • Nano copper-based catalyst and preparation method thereof

    CN108554407A

  • Carbon-doped silicon dioxide loaded nickel-copper alloy and preparation method and application thereof

    CN113351214A